Pengaruh Penerapan Kantin Sehat terhadap Karakter Siswa di SDN-SN Kuripan Banjarmasin - Tati'ah Tati'ah (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2020)
The purpose of this study was to determine the effect of the application of healthy canteens to the character of students in SDN-SN Kuripan 2 Banjarmasin. The object of this study was the effect of the application of healthy canteens to the character of students in SDN-SN kuripan 2 Banjarmasin, while the subjects in this study were SDN-SN students Excerpt 2 Banjarmasin. The research sample was 10 students in IVC class and 10 students in VA class. The method used is descriptive quantitative, using data digging tools, namely: Questionnaire, and documentation. Data analysis techniques are: Simple Linear Regression, and Conclusions. The conclusions of the study of the influence of the application of healthy canteens to the character of students in SDN-SN excerpts 2 Banjarmasin are as follows: tcount; ttable at a 5% significant level of 3,14; 1,697. Thus there is the effect of the application of healthy canteens to the character of students in the National Standard State School Curriculum 2 Banjarmasin. Based on the results of the study it is recommended that school residents, especially teachers and hawker sellers in the canteen should always provide ethical and moral learning to their students, so that students are expected to have good dedication and health, as well as teach students about the importance of independence from an early age, accustoming students to throw trash in places that have been provided in each of the canteens, responsibility with the school environment includes taking care of cleaning the school canteen.